Inhibitory effect of kopsia singapurensis extract on the corrosion behavior of mild steel in acid media - Raja, P.B.; Rahim, A.A.; Osman, H.; Awang, Khalijah (Peking Univ Press, 2010)
The influence of the alkaloid extract of Kopsia singapurensis on the corrosion behavior of mild steel (MS) in 1 mol . L-1 HCl and 1 mol . L-1 H2SO4 was studied using electrochemical techniques, viz., potentiodynamic polarization and AC impedance. The experimental results clearly show that the plant extract effectively inhibits corrosion in both acid media and the inhibition efficiency obtained from the electrochemical techniques is in good agreement. Furthermore, the polarization technique indicates that the extract acts as an anodic type inhibitor in HCl and as a mixed type in H2SO4. Scanning electron microscopy (SEM) was carried out to examine the surface morphological changes of metal specimens in both the inhibited and uninhibited solutions. SEM images show the formation of an adsorbed layer over the metal surface by the inhibitor molecule. The presence of alkaloidal constituents in the plant extract was confirmed by Fourier transform infrared (FTIR) spectroscopy and chemical analysis.